2018
DOI: 10.3390/app8060929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metallic Waste Addition on the Physical and Mechanical Properties of Cement-Based Mortars

Abstract: Featured Application: The development of advance construction materials based on waste valorisation is a reality. The cement-based mortar with recycled metallic waste presented in this study could be potentially used as a building material with crack self-monitoring properties.Abstract: This paper investigates the influence of the type and amount of recycled metallic waste on the physical and mechanical properties of cement-based mortars. The physical and mechanical properties of cement mortars, containing fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…When HESF and coarse aggregates are used, ITZs are created and the elasticity moduli based on static (compressive method) and dynamic (IET method) provide slight different values. This indicates that a correlation between Ed and Es is not provided, as also reported by Norambuena-Contreras et al 44 This suggests that inside the samples, a random fiber distribution is potentially constituted. 44,45 Figure 2(b) shows the correlation evidencing an exponential dependence of the tensile property with compressive strength (expressed by TS ¼ k CS 0.5 ).…”
Section: Hardened Properties Of Examined Scc Samplessupporting
confidence: 53%
See 3 more Smart Citations
“…When HESF and coarse aggregates are used, ITZs are created and the elasticity moduli based on static (compressive method) and dynamic (IET method) provide slight different values. This indicates that a correlation between Ed and Es is not provided, as also reported by Norambuena-Contreras et al 44 This suggests that inside the samples, a random fiber distribution is potentially constituted. 44,45 Figure 2(b) shows the correlation evidencing an exponential dependence of the tensile property with compressive strength (expressed by TS ¼ k CS 0.5 ).…”
Section: Hardened Properties Of Examined Scc Samplessupporting
confidence: 53%
“…This indicates that a correlation between Ed and Es is not provided, as also reported by Norambuena-Contreras et al 44 This suggests that inside the samples, a random fiber distribution is potentially constituted. 44,45 Figure 2(b) shows the correlation evidencing an exponential dependence of the tensile property with compressive strength (expressed by TS ¼ k CS 0.5 ). Angelin et al, 39 Khatri et al, 46 Ramli and Dawood 47 and Xavier et al 11 have reported similar correlations when rubber, furnace slag/fly ash, flowable high strength mortar and MG contents are utilized, respectively.…”
Section: Hardened Properties Of Examined Scc Samplessupporting
confidence: 53%
See 2 more Smart Citations
“…SEM results indicate the dense formation of SWCNT in cement matrix which will fll up the cement pores and act as a bridge to increase the load carrying capacity of the composite. Te addition of nanomaterials also arrests the formation of cracks and reduces the shrinkage of cracks [3,20]. But the increase of SWCNT concentration leads to agglomeration in the cement matrix at certain places as shown in red color in Figure 3, which will reduce the load capacity and lead to decrease in fexural strength.…”
Section: Methodsmentioning
confidence: 99%